(3cJGH aj GdWHs
(3ChdgG (B:s
(3GdZQV ef gPg GdQSGdI Cf jLeY ef GdcJH GdWHjI GdYQHjI hGdYHQGfjI hGdjhfGfjI hGdCaQfLjI eG jJYdb HGdeHGMKI ef ChLGY GdeaGUd NUhUkG GdfbQS s
(3BNQgG (B:s
(3heMUd GdcdGe Cfg ef CQGO GdJMQR adGHO Cf jchf Ydi GddjfI hCf dGjLGeY cKjQkG hdG jCcd cKjQkG s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs